MYTHOPOETIC RECONSTRUCTION OF GENDERED AND ECOLOGICAL SPACES IN THE FICTION OF SARAH JOSEPH - Vivek Malik, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2026)
This paper examines the mythopoetic reconstruction of gendered and ecological spaces in Sarah Joseph's major fictional works, including Gift in Green, Aalahayude Penmakkal, Othappu, Mattathi, and selected short stories. Drawing on ecofeminist, postcolonial feminist, and spatial-critical frameworks, the study investigates how Joseph transforms landscapes lagoons, garbage dumps, slums, convents, forests into sites of feminist resistance, ecological memory, and spiritual contestation against patriarchal and developmentalist paradigms. Through close textual analysis, the paper demonstrates that Joseph's mythopoesis operates as a dual strategy: first, by critically reworking Christian and epic myths that have historically legitimated gendered and environmental violence; and second, by constructing syncretic eco-spiritual narratives grounded in the embodied knowledge and spatial practices of marginalised communities in Kerala. The analysis reveals how Joseph's reconstructed spaces function as "counter-sites" where women's relationships with water, waste, domesticity, and sacred geography challenge both the masculinist logic of mastery over nature and the spatial architectures through which patriarchy regulates female mobility, desire, and subjectivity. Drawing on Vandana Shiva's critique of maldevelopment and Val Plumwood's analysis of dualistic thinking, the study situates Joseph's fiction within broader ecofeminist debates about the structural connections between oppression of women, exploitation of nature, and marginalisation of Third World communities under capitalist modernity. The paper further examines how ecological memory functions in Joseph's narratives as a political resource, preserving subaltern knowledges of environmental change while documenting the gradual violence of urbanisation, pollution, and land acquisition. By attending to Joseph's ecofeminist stylistics her use of colloquial registers, sensory detail, child narrators, and non-linear temporalities the analysis shows how linguistic and formal choices themselves participate in the mythopoetic reconstruction of space. The findings underscore Joseph's significant contribution to Indian ecofeminist literature, demonstrating how her work provides both a searing critique of contemporary socio-environmental crises in Kerala and a mythopoetic vision of more just and sustainable ecological futures rooted in feminist solidarities and indigenous spiritualities.